Knowledge, attitudes, and practices of health providers regarding access to and use of contraceptive methods among adolescents and youth in urban Guinea - Sidibé, Sidikiba; Kolié, Delphin; Grovogui, Fassou Mathias; Kourouma, Karifa; Camara, Bienvenu Salim; Delamou, Alexandre; Kouanda, Seni (Frontiers in Public Health, 2022)
Introduction The objective of this study was to analyze providers' knowledge, attitudes, and practices regarding access to and use of contraception by urban adolescents and youth. Methods This is a cross-sectional study of 1,707 health care providers in 173 selected private and public health facilities in the capital city of Conakry and the seven administrative regions of Guinea. Factors associated with health care providers' attitudes and practices were then analyzed using logistic regression. Results Among the 1,707 health providers, 71% had a good level of Knowledge about modern contraceptive use among adolescents and youth. In addition, 62% had positive attitudes, and 41% had good prescribing practices toward using modern contraceptive methods by adolescents and youth. Being a midwife (aOR: 1.39, 95%CI: 1.02–1.89), Being aged 25–34 years (aOR: 1.7, 95%CI: 1.2–2.3), 35–44 years (aOR: 2.1, 95%CI: 1.4–3.0), and 45 years, and older (aOR: 2.4, 95%CI: 1.3–4.2), an increase of years in professional experience (aOR:1.05; 95%CI: 1.02–1.08) were factors significantly associated with provider positive attitudes. However, being a medical doctor (aOR: 2.37, 95%CI: 1.04–4.42), an increase of years in professional experience (aOR: 1.07; 95%CI: 1.04–1.10) and a positive attitude (aOR: 3.16. 95%CI: 2.48–4.01) were factors associated with good practice in delivering modern contraceptive methods to adolescents and youth. Conclusion Positive attitudes and good practices toward the use of contraceptive services by adolescents and youth were found among providers. However, many health care providers still have unfavorable attitudes and practices toward delivering FP services to urban adolescents and youth. Therefore, future intervention programs should focus on training health care providers in youth- and adolescent-friendly reproductive health services and promoting contraception among adolescents.